Influence of wire rolling on Zircalloy-2: tensile behaviour and microstructural investigation - Singh R.K.; Goel S.; Kumar N.; Sunil B.D.Y.; Kumari S.; Eldin S.M.; Saxena K.K. (My University, 2025)
In the present work, the microstructure, tensile and texture properties of Zircalloy-2 (Zr-2) processed by the room temperature wire rolling (RTWR) have been investigated. The detail microstructural investigation was performed with the help of optical microscopy, Transmission Electron Microscopy (TEM) and Electron Back Scattered Diffraction (EBSD). Dislocation density was calculated by using X-ray diffraction (XRD) through modified Williamson Hall technique. The dislocation density increased as the true strain increased from 0.69 to 1.32, but at the same time when true strain increased from 1.32 to 2.77, dislocations density start decreasing. It was occurred due to the formation of large volume fraction of dynamic recrystallization grains (DRX) after inducing true strain of 2.77. The maximum yield strength of 750 MPa was achieved after true strain of 1.32, but as the induced true strain increased to 2.77, the yield strength decreased to 620 MPa. It was due to the formation of high volume fraction of DRX grain and grain coarsening led by the dislocations annihilation mechanism. The highest ductility was achieved after true strain of 2.77 is attributed to domination of dislocations annihilation assisted mechanism. The EBSD and tensile test investigation further confirmed the presence of Extension twinning ({101¯2}<101¯1>) after inducing a true strain of 1.32 and more, which signify the severe deformation through the RTWR. Further, deformation mechanism of Zr-2 alloy has been proposed through processing by RTWR with the help of experimental investigation. © 2023 The Author(s)